Significant improvements in clinical outcome measures and patient satisfaction after combined all-arthroscopic meniscal allograft transplantation and autologous chondrocyte implantation: a single-centre longitudinal study - Pawelczyk, Johannes; Fanourgiakis, Ilias; Feil, Sven; Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2024)
Purpose: The optimal treatment approach for the complex pathology of meniscal insufficiency and coexisting full-thickness cartilage defects remains unclear. The purpose of this study was to evaluate the viability, safety, and efficacy of this combined surgical approach at medium-term follow-up. Methods: This is a single-centre longitudinal study with blinded outcome assessment. All consecutive patients treated with combined all-arthroscopic meniscal allograft transplantation (MAT) with bone bridge fixation and ACI using chondrospheres at our institution between 2001 and 2021 were eligible for inclusion. Twenty patients with an average follow-up of 72.6 ± 34.4 months were included in the statistical analysis. Clinical outcomes were assessed pre- and postoperatively using the IKDC Subjective Knee Form, Lysholm Score, Tegner Activity Scale, KOOS, and Visual Analog Scale (VAS) for patient satisfaction. Failure and reoperation rates were assessed, and cartilage regeneration tissue was evaluated on postoperative MRI. Results: IKDC scores significantly improved from 52.1 ± 16.9 to 68.5 ± 16.3 (p = 0.003). Lysholm scores improved from 61.5 ± 21.7 to 78.5 ± 12.9 (p = 0.004). Tegner scores improved from 3.5 (1-4) to 4.0 (2-6) (p = 0.014). KOOS scores improved significantly across all subcategories, except ‘symptoms’, where improvements did not reach statistical significance. VAS for overall patient satisfaction showed improvements but did not reach statistical significance. The combined procedure was successful in 17 patients (85%). Eight patients had to undergo reoperation (40%), comprising mostly small, arthroscopic procedures. Seven reoperations were directly attributable to meniscal allograft transplantation (46.7%). Postoperative Magnetic Resonance Observation of Cartilage Repair Tissue scores were 68.9 ± 16.8 (n = 14). Conclusion: Combined arthroscopic MAT and autologous chondrocyte implantation (ACI) is a viable, safe, and effective treatment approach for younger patients with meniscal insufficiency and coexisting full-thickness cartilage damage, where alternative treatment options are limited. The combined surgical procedure achieved significant improvements in clinical outcome measures and patient satisfaction with acceptable failure and high arthroscopic reoperation rates. MAT is the limiting part of this combined procedure, with most failures and reoperations being attributable to MAT, as opposed to ACI. Level of Evidence: Level III.
Gesehen am 28.03.2024